Evaluation of 3D high resolution images using inexpensive distributed parallel system - Eren, Haluk; Celik, Uemit; Poyraz, Mustafa (Ieee, 2007)
In the telesurgery operations, images should be high resolution and processed in real time. It seems difficult to accomplish this process in real time using only one computer. In our study, we propose to get 3d scene images inside and outside of surgery environment in real time and transfer them into different places. As known, 3d reconstruction needs intensive calculations. Nowadays, using distributed parallel systems are getting increase. Therefore, we investigate the performance rates using a group of inexpensive inert computers which work as a distributed parallel system supposed to be established in a medical environment.
IEEE 15th Signal Processing and Communications Applications Conference -- JUN 11-13, 2007 -- Eskisehir, TURKEY